2012
DOI: 10.1016/j.ijheatmasstransfer.2012.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady natural convection within a differentially heated enclosure of sinusoidal corrugated side walls

Abstract: a b s t r a c tNumerically investigation of natural convection within a differentially heated modified square enclosure with sinusoidally corrugated side walls has been performed for different values of Rayleigh number. The fluid inside the enclosure considered is air and is quiescent, initially. The top and bottom surfaces are flat and considered as adiabatic. Results reveal three main stages: an initial stage, a transitory or oscillatory stage and a steady stage for the development of natural convection flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Hydro-thermal performance in a corrugated channel with nanofluid was numerically examined in [ 24 ]. As was shown by Hasan et al [ 25 ], the corrugation amplitude and frequency have a significant impact on the heat transfer rate in natural convection for a deferentially-heated cavity. Hussain et al [ 26 ] numerically examined the natural convection in a tilted sinusoidal corrugated cavity with magnetic field effects.…”
Section: Introductionmentioning
confidence: 86%
“…Hydro-thermal performance in a corrugated channel with nanofluid was numerically examined in [ 24 ]. As was shown by Hasan et al [ 25 ], the corrugation amplitude and frequency have a significant impact on the heat transfer rate in natural convection for a deferentially-heated cavity. Hussain et al [ 26 ] numerically examined the natural convection in a tilted sinusoidal corrugated cavity with magnetic field effects.…”
Section: Introductionmentioning
confidence: 86%
“…The effect of a corrugated side wall on the natural convection of a differentially heated cavity was investigated in Ref. [16] by using the finite element method. Their results showed that the heat transfer is greatly influenced by the variation corrugation amplitude and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…compact heat exchangers [8] and cooling systems [9,10], selective laser melting process [11]). Although quite some various different configurations of the enclosure problem are possible [12][13][14][15][16][17][18], one of the most studied cases involves the two-dimensional square enclosure with differentially heated isothermal vertical walls and adiabatic horizontal walls [19,20]. When the vertical walls are insulated to ensure adiabatic conditions and the lower horizontal wall held at the higher temperature then one has the Rayleigh-Bénard configuration [21,22].…”
Section: Introductionmentioning
confidence: 99%